Analysing The Impact of Covid-19 On UK SMES and Strategies Adopted, A Study on SMES in The UK Hospitality Sector - Khurshidjon Sharofiddinov (Zien Journals, 2023)
This article analyses the impact of the COVID-19 pandemic on the hotel business and the economy as a whole. The hotel sector is considered an important source of income and job creation in many countries. The restrictive measures and closures caused by the pandemic have led to a significant reduction in revenue and problems for small and medium-sized enterprises in the industry. The purpose of the study is to determine the strategies and intentions adopted by the UK hotel industry during the crisis. A qualitative research approach will be used to collect data. Analysing the data, the authors show that hotel companies have faced immediate and long-term consequences of the pandemic, including closures, reduced revenues and problems with demand recovery. This study is useful for understanding the impact of COVID-19 on the hotel sector and the strategies adopted in the UK, especially for small and medium-sized enterprises in this industry.
Keywords: hotel business; pandemic; COVID-19